Rainfall and Temperature Perception among Farmers in India: A Study of Bundelkhand Region - Jatav, Surendra Singh (Journal of Sustainability and Environmental Management, 2022)
Climate change has impacted the crop yield and affected the livelihoods of the farmers. Using a systematic random sampling technique, 200 samples were collected from two districts, viz., Jhansi and Jalaun of Bundelkhand region, India from September to November 2017, while rainfall and temperature data were collected from 1969 to 2017 from the Indian Meteorological Department of India to find the link between farmers’ perception on rainfall & temperature, and district’s rainfall and temperature pattern in long-term.  Different statistical tools such as the Man Kendall test was employed to examine the rainfall and temperature trends, while the Breusch-Pagan test was used to check heteroscedasticity in the model. Further, the binary logistic regression model was also used to examine the determinants of farmers’ perceptions using socioeconomic variables. The results confirm based on the majority of the farmers’ perception that temperature has increased, while rainfall has declined. These results are in a similar line with the district’s rainfall and temperature trends. The regression results suggest that gender, education, and access to toilets are less likely to influence the farmers’ perception of climate change, while age, income, and access to electricity are significantly likely to influence the farmers’ perception of climate change. Hence, policy should be implemented to enhance rural farming communities’ awareness of climate change by providing training and creating awareness.